Directional and controllable edge-emitting ZnO ultraviolet random laser diodes - Yu, S. F. (2011)
Room-temperature ultraviolet random lasing action is demonstrated from a p-GaN/annealed i-ZnO:Al(3%)/n-ZnO:Al(5%) buried heterojunction diode with a 2 μm rib waveguide. Excellent electrical-to-optical conversion efficiency is achieved by strong electrical and optical confinement of a buried heterojunction rib waveguide structure. Hence, emission intensity (threshold current) can be enhanced (reduced) by ∼ 9 times ( ∼ 40%). Directional emission as well as controllability on the number of the random lasing modes can also be achieved.